MiroRNA-127-3p targets XRCC3 to enhance the chemosensitivity of esophageal cancer cells to a novel phenanthroline-dione derivative. (October 2016) - Zhen, Ni; Yang, Qingyuan; Zheng, Kangdi; Han, Zeping; Sun, Fenyong; Mei, Wenjie; Yu, Yongchun
Abstract: MicroRNAs are small non-coding RNAs with 18–22 nucleotides in length and have been proposed to function in various biological processes by targeting genes for post-transcriptional degradation via their 3′ untranslated region. Moreover, they have been suggested to improve the chemosensitivity in a panel of tumors. However, the biological functions of microRNA-127-3p in esophageal carcinogenesis are still enigmatic. Thus, in the study, we firstly analyzed the roles of microRNA-127-3p in regulating the growth of esophageal cancer cells both in vitro and in vivo . Afterwards, using the microRNA-targeted gene prediction software and the dual-luciferase reporter assays, we confirmed that microRNA-127-3p specifically reduced the expression of X-ray repair complementing defective repair in Chinese hamster cells 3, one of RAD51 recombinase paralogs, at both mRNA and protein levels. Furthermore, using the homologous recombination repair and non-homologous end joining repair reporter systems, we found that microRNA-127-3p specifically compromised the homologous recombination repair and significantly increased DNA double strand breaks in cells. Besides, it statistically increased the chemosensitivity of esophageal cancer cells to a novel phenanthroline-dione derivative in vivo by mechanistically impairing the recruitment of RAD51 to the damage sites. In summary, our findings not only suggest that microRNA-127-3p can be used as a predictor for evaluating the development of esophageal carcinoma, but also show that it can be used to increase the chemosensitivity of esophageal cancer patients to the phenanthroline-dione derivative, which might be a potential anticancer candidate in the future.